2020
DOI: 10.14336/ad.2019.0621
|View full text |Cite
|
Sign up to set email alerts
|

Dementia Risk in Type 2 Diabetes Patients: Acarbose Use and Its Joint Effects with Metformin and Pioglitazone

Abstract: This population-based retrospective cohort study investigated dementia risk associated with acarbose in patients with type 2 diabetes mellitus by using Taiwan's National Health Insurance database. A cohort of 15,524 matched pairs of ever and never users of acarbose based on propensity score matching was enrolled from new-onset type 2 diabetes patients from 1999 to 2006. Patients who were alive on January 1, 2007, were followed up for dementia until December 31, 2011. Adjusted hazard ratios were estimated using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Heart failure [ 34 ], atrial fibrillation [ 35 ], chronic obstructive pulmonary disease [ 36 ], osteoporosis [ 37 ], dementia [ 38 ], inflammatory bowel diseaese [ 39 ], and varicocele [ 40 ] have been associated with a higher incidence of ED in humans. Except for varicocele, our previous analyses supported a lower risk of all these morbidities among metformin users [ 6 7 8 11 12 15 16 ]. Although the effect of metformin on varicocele has not been studied, it is highly possible that metformin may reduce the risk of varicocele (another form of venous dilatation involving the testicles) because metformin has been shown to reduce the risk of venous diseases of varicose veins [ 9 ] and hemorrhoid [ 10 ].…”
Section: Men's Reproductive Healthmentioning
confidence: 58%
See 1 more Smart Citation
“…Heart failure [ 34 ], atrial fibrillation [ 35 ], chronic obstructive pulmonary disease [ 36 ], osteoporosis [ 37 ], dementia [ 38 ], inflammatory bowel diseaese [ 39 ], and varicocele [ 40 ] have been associated with a higher incidence of ED in humans. Except for varicocele, our previous analyses supported a lower risk of all these morbidities among metformin users [ 6 7 8 11 12 15 16 ]. Although the effect of metformin on varicocele has not been studied, it is highly possible that metformin may reduce the risk of varicocele (another form of venous dilatation involving the testicles) because metformin has been shown to reduce the risk of venous diseases of varicose veins [ 9 ] and hemorrhoid [ 10 ].…”
Section: Men's Reproductive Healthmentioning
confidence: 58%
“…Metformin exerts various beneficial effects beyond glucose lowering, including immune modulation, anti-atherosclerosis, anti-cancer, anti-aging, anti-microbia, and anti-inflammation [ 3 4 ]. Recently, by using the nation-wide database of the National Health Insurance in Taiwan, we also showed that metformin use is associated with a lower risk of hypertension [ 5 ], hospitalization for heart failure [ 6 ], hospitalization for atrial fibrillation [ 7 ], chronic obstructive pulmonary disease [ 8 ], varicose veins [ 9 ], hemorrhoid [ 10 ], dementia [ 11 12 ], nodular goiter [ 13 ], uterine leiomyoma [ 14 ], osteoporosis/vertebral fracture [ 15 ], and inflammatory bowel disease [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…First, together with our previous studies that do not suggest an increased risk of bladder cancer [ 30 ], ovarian cancer [ 31 ], oral cancer [ 32 ], kidney cancer [ 33 ], thyroid cancer [ 34 ], lung cancer [ 35 ] and prostate cancer [ 36 ] associated with pioglitazone use, the public health concern of an increased cancer risk associated with pioglitazone can be relieved and should not impede the clinical use of pioglitazone. Second, the potential benefits of pioglitazone on the improvement of lipid profile [ 37 ], the risk reduction of dementia [ 38 , 39 ], chronic obstructive pulmonary disease [ 40 ], non-alcoholic fatty liver disease [ 41 ], stroke [ 2 ] and cardiovascular disease [ 42 ] and the usefulness of pioglitazone in the treatment of polycystic ovarian syndrome in women [ 43 ] suggest that some patients may gain pleiotropic benefits beyond glycemic control from the appropriate use of pioglitazone.…”
Section: Discussionmentioning
confidence: 99%
“…As pointed out by a recent article discussed by Baker et al, up to now, "there are no data to suggest that metformin should not be initiated soon after the diagnosis of diabetes", even in the era of these novel antidiabetic drugs [56]. Our previous pharmaco-epidemiological studies conducted in Taiwan suggest that metformin not only reduces cancer risk, but also the risk of various non-malignant diseases such as hypertension [58], heart failure [59], atrial fibrillation [60], chronic obstructive pulmonary disease [61], pulmonary tuberculosis infection [62], Helicobacter pylori infection [63], varicose veins [64], acute appendicitis [65], hemorrhoids [66], dementia [67,68], nodular goiter [69], uterine leiomyoma [70], osteoporosis/vertebral fracture [71], and inflammatory bowel disease [72]. We also found that metformin ever users have a lower risk of total mortality than never users of metformin, with an estimated multivariate-adjusted hazard ratio of 0.67 (95% confidence interval: 0.64-0.69) [72].…”
Section: Discussionmentioning
confidence: 99%